INTEGRASI NILAI-NILAI ISLAM DALAM PEMANFAATAN MEDIA DIGITAL DAN ARTIFICIAL INTELLIGENCE DI ERA TEKNOLOGI MODERN - Intan Nurrisma, Intan; Inayatillah (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
The development of digital media and Artificial Intelligence (AI) has brought fundamental changes to various aspects of human life, including education, da’wah, and religious practices. On the one hand, digital technology provides easier access to information, learning efficiency, and opportunities for the transformation of Islamic education. On the other hand, it also g presents serious challenges in the form of ethical crises, moral degradation, dehumanization, and the potential distortion of spiritual values. This article aims to analyze the integration of Islamic values in the utilization of digital media and AI in the modern technological era as an effort to maintain a balance between technological advancement and human values. This study employs a qualitative approach using a library research method by examining primary and secondary sources, including the Qur’an, Hadith, classical Islamic texts, and contemporary scholarly literature related to Islamic ethics and technology. The discussion reveals that Islamic values such as tawhid, trust (amanah), justice, responsibility, and noble character, grounded in the framework of maqāṣid al-sharī‘ah, can serve as an ethical foundation for the development and utilization of digital media and AI. The integration of these values is essential to ensure that technology functions as a means of public welfare rather than merely a tool of technical efficiency, thereby remaining aligned with Islamic spiritual and humanitarian objectives.